THE EFFECTS OF POPULAR PRO-SOCIAL BEHAVIOUR CHILDREN ON PEERS AND SCHOOL ENVIRONMENT - Diah Ningrum (Dialectical Literature and Educational Journal, 2019)
The aims of the study were to find out the effects of popular pro-social children on peers and school environment. Mixed methods were used in the present study which had two phases; quantitative method and qualitative method. Peer matrix of peer nomination was used as data collection in quantitative, meanwhile interview was used in qualitative method. The results revealed that 5 popular children obtained from peer matrix of peer nomination were liked most by peers. The Results indicated that popular children gave effects on peers and school environment. Popular children influenced their peers and school environment in pro-social behaviour, leadership, and academic achievement. Meanwhile, besides in academic achievement homeroom teachers also agreed on the effects of popular children in pro-social behaviour.